Case Report of a Patient with Jejunal Diverticulitis as a Cause of Acute Abdomen - Daniel Morales Salgado; Flor Alexia Santana Aguillón (International Journal of Medical Science and Clinical Research Studies, 2026)
Jejunal diverticulitis is an uncommon condition that may lead to serious complications such as abscess, perforation, or intestinal obstruction, constituting an unusual cause of acute abdomen. We present the case of a male patient in his sixth decade of life with acute abdomen secondary to acute diverticulitis who required urgent surgical management. Computed tomography is the imaging study of choice, and treatment depends on the patient’s clinical condition.